(untitled) (ENTHYMEMA, 2023)
This article discusses Crime and Punishment with the objectives to: 1. analyze Raskolnikov’s project: to kill not a person, but a “principle”, that is the need for the Law in society; 2. explain the meaning of his gesture: killing the Law is an even more radical gesture than “the death of God” described by Nietzsche; 3. clarify the motive(s) for Raskolnikov’s action, adopting the theories of desire and the polysemy of identity. What drives Raskolnikov is the desire to be, an indispensable concept after Freud, but one which requires investigation on a philosophical level. If, undoubtedly, Raskolnikov’s first motive is the wish to affirm the distinction between ordinary and “extraordinary” men, there is, however, a second, less visible motive, which consists in trying to sever a deeper dependence, that with his mother. Crime and Punishment is alsothe novel of matricide. 4. The extraordinary semantic density of Dostoevsky’s prose is reached through relationships: he is the master of overcoming and ambivalence. Analyzing the fabric of relationships in Dostoevsky highlights the importance of the female figures belonging to the series of mothers and to the series of daughters, which can only be understood through a logic of overcoming, and its unsettling outcomes. 5. Finally, contrary to a common tendency to separate the content (the ideas) in Dostoevsky from the artistic form, this article affirms that a) in Dostoevsky there are no ideas: if anything, there is the Idea, as a manifestation of the Sublime; b) in Dostoevsky there are no idea-concepts, but only characters.